Efficacy of Stabilization Exercise for Neck Pain: A Narrative Review and Meta-Analysis of Randomized Controlled Studies - Zang, Cheng; Zhou, Yanyan; Liu, Yonghui; Wu, Binbin (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
Introduction Stabilization exercise may be an important approach to alleviate neck pain. However, its use has not been well established. We conduct a narrative review and meta-analysis to evaluate the efficacy of stabilization exercise to control neck pain.Methods PubMed, Embase, and the Cochrane Central Register of Controlled Trials are searched. Randomized controlled trials (RCTs) assessing the influence of stabilization exercise on neck pain are included. Two investigators independently have searched articles, extracted data, and assessed the quality of included studies. Meta-analysis is performed using the random-effect model.Results Five RCTs involving 217 patients are included in the meta-analysis. Compared with control intervention for neck pain, stabilization exercises has no notable impact on pain intensity (Std. MD=−0.55; 95% CI=−1.24 to 0.14; P=0.12), neck disability index (Std. MD=−0.44; 95% CI=−1.01 to 0.13; P=0.13), SF-36 physical health (Std. MD=−0.18; 95% CI=−0.61 to 0.26; P=0.43), SF-36 mental health (Std. MD=−0.03; 95% CI=−0.47 to 0.41; P=0.89), but can remarkably decrease depression scale (Std. MD=−1.05; 95% CI=−1.59 to −0.50; P=0.0002).Conclusions Stabilization exercises shows similar impact on pain intensity, neck disability index, SF-36 physical health and SF-36 mental health, but significant reduced depression scale compared with control intervention in patients with neck pain.
Keywords: stabilization exercises; neck pain; pain intensity; randomized controlled trials.